R-Ras-Akt axis induces endothelial lumenogenesis and regulates the patency of regenerating vasculature - Fangfei Li (Nature Portfolio, 2017)
Formation of the vascular lumen initiates the blood flow and it is crucial for tissue homeostasis. Here, Li et. al show that the R-Ras-Akt signaling axis is crucial for reparative angiogenesis in mice because it stabilizes the microtubule cytoskeleton in endothelial cells to promote endothelial lumen formation.